Association of Serum Irisin With Severity and Prognosis in Patients With Coronavirus Disease 2019: A Prospective Cohort Study - Zhang X; Wang W; Li Y; Liu X; Zhang L; Cheng Z; Liu M; Wang Y; Fu L; Yang J (International Journal of General Medicine)
Xinli Zhang,1,2,* Wennan Wang,1,3,* Ye Li,2 Xiaoning Liu,2 Liangzhu Zhang,2 Zhenyu Cheng,1,4 Mingyan Liu,1,4 Yu Wang,1,4 Lin Fu,1,4 Jin Yang1,4,5 1Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 2The First Department of Tuberculosis, Anhui Chest Hospital, Hefei, Anhui Province, People’s Republic of China; 3The Fifth Department of Tuberculosis, Anhui Chest Hospital, Hefei, Anhui Province, People’s Republic of China; 4Institute of Respiratory Diseases, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China; 5Information Management Center, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lin Fu; Jin Yang, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, People’s Republic of China, Email fulindev@126.com; yangqj1015@foxmail.comBackground: Irisin is the cleaved form of fibronectin type III domain-containing protein 5 (FNDC5), which can confer antioxidant and anti-inflammatory effects. Several studies have revealed that irisin can alleviate lung injury and affect the pathology of coronavirus disease 2019 (COVID-19). The aim of this study was to assess the relationships of serum irisin with the severity and prognosis of COVID-19.Methods: A total of 328 COVID-19 patients were recruited. Peripheral blood samples were collected. The level of serum irisin was determined by ELISA. The associations of serum irisin with COVID-19 severity and prognosis were evaluated through linear and logistic regression models on the basis of a prospective cohort study.Results: Serum irisin levels were lower in severe patients than in mild patients. The level of serum irisin was gradually decreased with the worsening of COVID-19. Spearman correlation analysis revealed that serum irisin concentration was inversely correlated with several clinical characteristics. Moreover, linear and logistic regression analyses revealed that serum irisin concentration was negatively correlated with the severity score. Interestingly, chronic heart and kidney diseases significantly affected the associations between serum irisin and severity scores. The results of the follow-up study suggested that the level of serum irisin upon admission was reduced in patients who died within one month of hospitalization. A lower serum irisin level at admission increased the risk of death within one month.Conclusion: Serum irisin levels at admission were negatively correlated with disease severity and prognosis, suggesting that irisin is involved in the pathological process of COVID-19. Serum irisin may be used as a biomarker for diagnostic and prognostic assessment of COVID-19.Keywords: COVID-19, irisin, severity scores, prognostic outcomes, cohort study